Hostages of the mythological mind or why was became possible the conflict of Eastern Ukrainian - Belokobylskiy, Aleksandr (Skhid, 2015)
The article examines the situation of the existential threat, connected with the destruction of social reality. Suggested that the threat to the structural part of the reality, which was formed on the basis of religious and mythological forms of social existence, is seen as an occasion for self-protection. Targeted external influence on human consciousness lead to the formation of ersatz realities in which "the struggle for values" represents only a rationalized form pre-rational commitment to preserving identity.